Pengaruh Kualitas Pelayanan Terhadap Loyalitas Melalui Kepuasan Nasabah Tabungan Sebagai Variabel Intervening Pada PT. Bank Negara Indonesia Tbk, Cabang Malang (Studi Pada Nasabah PT. Bank Negara Indonesia Tbk, Cabang Malang) - Edi Cahyono; Rois Arifin; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
Abstract The purpose of this study was to determine the effect of service quality on loyalty through savings customer satisfaction as an intervening veriable at PT. Bank Negara Indonesia Tbk, Malang Branch. The population in this study are savings customers who often make transactions either directly come to the office or only transact through an ATM machine at PT. Bank Negara Indonesia Tbk, Malang Branch. This study is a type of research in which researchers observe data collection and record, analyze, and interpret data as is. The research method used is multiple linear regression. The sample in this study was taken using judgmental sampling by selecting people who were selected so that they were seen as having a close connection with the special characteristics of the sample that were already known.The analysis shows that the direct effect between service quality on customer loyalty is equal to 0.252 and the direct effect on satisfaction on customer loyalty is equal to 0.399. The influence directly shows that with increasing service quality, customer loyalty will increase. The results of the analysis of the direct effect can be seen that the decision affects the loyalty that is equal to 0.399. Keywords : Service Quality, Customer Satisfaction and Customer Loyalty